2017
DOI: 10.22159/ajpcr.2017.v10i4.16269
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Docking Studies of Gallic Acid Structural Analogues as BCL-Xl Inhibitor in Cancer

Abstract: Objective: Apoptosis, or programed cell death, forms an important part of the cellular regulation machinery. The Bcl-2 protein family, comprising proapoptotic and antiapoptotic members, forms an important part of the cells internal apoptotic pathway. Overexpression of the antiapoptotic members of the family in a number of cancer cell lines renders them immune to apoptosis and the ability to survive under conditions of cellular stress. Inhibition of the antiapoptotic members of the Bcl-2 family like Bcl-XL is, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The effect of heptyl gallate and octyl gallate on primary endometriosis cells toward pro-inflammatory cytokines IL-1β in this study showed Based on the results of in silico docking analysis, the docking energy (binding energy score/∆G) of gallic acid compounds, heptyl gallate and octyl gallate as ligand against protein NFkB targets respectively −7.66 kkal/mol, −7.68 kkal/mol and −7.98 kkal/mol. ∆G shows the strength of the ligand affinity with the target protein, in which the higher of the negative ∆G value the interaction and conformation between ligand and protein will be more constant and stable [19]. In this study, the octyl gallate showed a stronger and more stable affinity toward NFKB than heptyl gallate and gallic acid.…”
Section: Resultsmentioning
confidence: 58%
“…The effect of heptyl gallate and octyl gallate on primary endometriosis cells toward pro-inflammatory cytokines IL-1β in this study showed Based on the results of in silico docking analysis, the docking energy (binding energy score/∆G) of gallic acid compounds, heptyl gallate and octyl gallate as ligand against protein NFkB targets respectively −7.66 kkal/mol, −7.68 kkal/mol and −7.98 kkal/mol. ∆G shows the strength of the ligand affinity with the target protein, in which the higher of the negative ∆G value the interaction and conformation between ligand and protein will be more constant and stable [19]. In this study, the octyl gallate showed a stronger and more stable affinity toward NFKB than heptyl gallate and gallic acid.…”
Section: Resultsmentioning
confidence: 58%
“…5). Ligands 11,15, and, to a lesser extent, 12, showed strong interactions with the enzyme active site.…”
Section: Interaction Dynamicsmentioning
confidence: 94%
“…Molecular docking simulations can be used to quickly screen a database of chemical compounds for potential drug molecules. Indeed, many studies have been performed in which molecular docking was used to discover potential anticancer agents, including the screening of potent (peroxisome proliferator-activated receptor-gamma) agonists from natural resources [12], the screening of potential BRCA1 inhibitors [13], docking studies on the interactions of eriodictyol with apoptotic proteins [14], and the development of gallic acid structural analogs as BCL-XL inhibitors [15].…”
Section: Introductionmentioning
confidence: 99%
“… 15 According to in silico study, gallic acid and its derivatives (alkyl ester) can be BRAF inhibitor of colorectal cancer, 16 as well as inhibitor of the anti-apoptosis protein Bcl-xL in breast cancer. 17 , 18 In addition, gallic acid derivative compounds (N-alkyl gallamide) have strong cytotoxic activity on MCF7 breast cancer cells, and colorectal cancer cells, HCT 116. 19 , 20 This study aims to design gallic acid derivative compounds (N-alkyl Gallamide), analyze molecular modeling of target proteins associated with breast cancer, and determine the ADMET profile of these compounds as apoptosis agents of MCF-7 breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%